Vibrant Vietnam : Forging the Foundation of a High-Income Economy - World Bank Group (World Bank, Hanoi, 2020)
Vietnam’s development strategy requires an urgent upgrade. Past growth has been impressive. But as a favorable domestic and international environment changes, future growth must be productivity-driven—obtaining more and higher quality output from firms, infrastructure, workers and natural resources. The World Bank’s Vibrant Vietnam report discusses priorities for an upgraded growth model based on extensive consultations, international experience and academic findings.